Transmitting and receiving equipment for radiocommunication. Radio‑over‑fibre technologies and their performance standard. Radio-over-fibre-based indoor distributed antenna system (DAS) for 5G Part 4, (30th May 2023) - British Standards Institution,
No abstract available